Treatment policy for localized oral cancer - I. M. Gel’fand; I. S. Romanov; D. B. Udintsov (Опухоли головы и шеи)
This paper analyzes the results of treatment for disseminated oral cancer (T1N0M0). The combined (surgery and radiotherapy) treatment group demonstrated the best 5-year overall and relapse-free survival rates (96.6 and 92.3 %, respectively). In the surgery group only, these rates were lower, amounting to 79.2 and 68.7 %, respectively. The medical therapy group was noted to have the lowest 5-year overall and relapse-free survival rates (81.8 and 45.5 %, respectively).